Green marketing mix as a strategy to improve competitive advantage - Pavithra, S.; Pushpanathan, A. (Faculty of Management Studies and Commerce, University of Jaffna., 2019)
Today many companies want to improve their greenness. A way to do this is by greening the marketing mix. The current green marketing literature only touches upon certain aspects of the marketing mix. As green marketing strategy become increasingly more important to firms adhering to a triple-bottom line performance evaluation. The purpose of the study is to investigate how a company blends its greenness sense into their marketing mix and marketing strategy and the response from the customers toward corresponding aspects. Companies that use the extreme green strategy fully incorporate environmental issues and responsibility into their business strategies and address issues related to marketing mix for the environment. Strategic greening in one area may or may not be leveraged effectively in others. So, organizations must ensure that green marketing activities are assimilated holistically, especially if they are used in positioning or promotional activities. This paper discusses assimilation of green marketing and marketing mix by way of considering the 4 Ps of marketing as a strategy to improve competitive advantage.
Keywords: Green Marketing Mix; Green Strategy; Competitive Advantage